The Influence of English Teacher Education on Students' Character Development in Theoretical Perspective - Syafiq Khairi; Rahmasari; Riskha Zahwannisa (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Character education is a process of applying moral and religious values to students through science, the application of these values both to oneself, family, fellow friends, to educators and the surrounding environment and God Almighty. This article will discuss the influence of character education in various theoretical perspectives, the role of the school environment, family, and teachers in shaping student character, and strategies that can strengthen character education in the educational context. The research method used is descriptive method and qualitative approach. The findings of this study highlight the importance of theoretical models and approaches in understanding the role of parenting, religiosity and sociological factors in shaping student character. In addition, the article also discusses the positive relationship between extracurricular activities and character education, the important role of educators, and the impact of the school environment in shaping student character.